(untitled) (American Journal of Islam and Society, 2008)
On 14 May 2008, the Center for the Study of Islam and Democracy (CSID) held its ninth annual conference, entitled “Political Islam and Democracy: What Do Islamists and Islamic Movements Want?” at the Marriot Renaissance Hotel. This event brought together a distinguished group of experts to discuss the relationship between religion and democracy, the Muslim Brotherhood and democratic evolution, negotiating and implementing democracy in diverse contexts, and other related topics. The first session, which included Nelly Lahoud (professor of political theory, Goucher College), Mark Gould (professor of sociology, Haverford College), and Amr Hamzawy (senior associate, Carnegie Endowment for International Peace) raised such issues as dismissing the idea that Islam and democracy are mutually exclusive and discrediting the terrorists who have hijacked Islam and turned it into the very things it stands against: radicalism, closed-mindedness, intolerance, and violence. Gould discussed “Sovereignty of God: Constitutional Processes in Islam and Christianity,” and Hamzawy delved into an analysis of the Brotherhood’s draft party platform ...